YOUNG MEDIA CREATORS: PEMBERDAYAAN SISWA SMA MELALUI PELATIHAN JURNALISME VIDEO, FOTO, DAN PENULISAN BERITA BERBANTUAN KECERDASAN BUATAN - Rino Andreas; Siti Umaiyah; Septi Anggita Kriskartika; Rony Kurniawan Pratama; Muhamad Reznu Firsyawardana; Yudha Wirawanda (LPPM Institut Pendidikan Nusantara Global, 2026)
Artificial intelligence (AI) has transformed information production practices among senior high school students. Students of SMA Negeri 1 Pakem Yogyakarta have the potential to become critical, creative, and responsible young media creators, yet they still need guidance in producing journalistic content. This article describes the implementation of Young Media Creators as a student empowerment program through training in video journalism, journalistic photography, and AI-assisted news writing. The program used a participatory approach involving preparation, material delivery, production practice, mentoring, and evaluation. The training covered basic journalism, photo and video production, news writing, media ethics, and the use of AI. The results show improved journalistic understanding, media production skills, and ethical awareness in using AI to create school-based journalistic works. The main contribution of this program lies in the integration of basic journalistic competencies, media ethics, and the responsible use of AI technology. Students are encouraged to become media creators who are not only creative and productive, but also capable of critical thinking and understanding the ethical implications of using digital technology. This program contributes to the development of young human resources who are adaptive to digital transformation while also being able to produce high-quality information content that benefits society.